Development of Adventure-Based Educational Games to Improve Critical Thinking Skills and Interest in Learning - Regan Moro, Fabianus; Zamzam, Kenys Fadhilah (Program Studi Pendidikan Matematika Universitas PGRI Kanjuruhan Malang, 2025)
Games are widespread in society, not only among children but adults also play games. It is not uncommon for school-age children to play this game until late at night which of course interferes with their study time. In this study, the researcher developed an educational game called